2014
DOI: 10.1007/s00330-014-3284-9
|View full text |Cite
|
Sign up to set email alerts
|

Focal hemodynamic patterns of status epilepticus detected by susceptibility weighted imaging (SWI)

Abstract: • The focal ictal brain regions show hyperperfusion in DSC MR-perfusion imaging. • SWI shows focally diminished cortical veins in hyperperfused ictal regions. • SWI has the potential to identify a focal ictal region in CSE/NCSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
0
25
2
Order By: Relevance
“…A recently published report described an association of regional pseudo-narrowed or pseudo-diminished cortical veins in SWI and regional hyperperfusion in dynamic susceptibility contrast (DSC) MRI with ictal and post-ictal abnormalities on EEG. 7 In contrast, the present study demonstrated regionally prominent cortical veins in SWI associated with abnormalities on inter-ictal EEG. Blood oxygen level-dependent (BOLD) signals depend on cerebral blood flow (CBF), cerebral blood volume (CBV), and cerebral metabolic rate of oxygen (CMRO 2 ).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…A recently published report described an association of regional pseudo-narrowed or pseudo-diminished cortical veins in SWI and regional hyperperfusion in dynamic susceptibility contrast (DSC) MRI with ictal and post-ictal abnormalities on EEG. 7 In contrast, the present study demonstrated regionally prominent cortical veins in SWI associated with abnormalities on inter-ictal EEG. Blood oxygen level-dependent (BOLD) signals depend on cerebral blood flow (CBF), cerebral blood volume (CBV), and cerebral metabolic rate of oxygen (CMRO 2 ).…”
Section: Discussioncontrasting
confidence: 66%
“…10 We speculate that sufficiently strong seizures and concomitant increased CMRO 2 in the brain might result in decreased BOLD response and possible hypoxia under some circumstances. The present observations, along with recently published reports, 5,7 suggest a complex, non-linear relationship between BOLD signal and hemodynamic and neuronal activity under pathologic circumstances. We speculate that the simultaneous use of MRA with SWI could facilitate understanding of the correlation between cerebral perfusion and intravascular deoxygenated hemoglobin concentration in epileptic foci during the acute stage of convulsive disorders.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…18,27 In our population, acute/subacute MRI changes were present in only 12% of the patients studied with MRI during or after an episode of SE. 18,27 In our population, acute/subacute MRI changes were present in only 12% of the patients studied with MRI during or after an episode of SE.…”
Section: Discussionmentioning
confidence: 84%
“…Incidence of SE-related MRI signal alterations in retrospective series varies between 11.6% and 50%. 18,27 In our population, acute/subacute MRI changes were present in only 12% of the patients studied with MRI during or after an episode of SE. This low proportion is related mostly to the fact that only 35% of the patients received an MRI study during SE and most investigations were performed after cessation of the study.…”
Section: Discussionmentioning
confidence: 84%